Assessing Translation of Humor in The English Subtitles of Goodbye Mr. Loser - Xiaorui, Zheng; Amirdabbaghian, Amin (Journal of Digital Sociohumanities, 2024)
Humor is primarily influenced by both the source and target language cultures, which poses significant challenges for translators. Given the continuous emergence of comedy movies, humor plays a crucial role in cultural expression. However, research on the assessment of translation quality of humor in movie subtitles in China remains limited. This study aims to categorize the translation techniques using Pedersen’s typology (2005, 2011) and assess the translation quality of the humorous content in the English subtitles of the Chinese comedy movie Goodbye, Mr. Loser (2015). Goodbye, Mr. Loser is one of the most successful comedy movies in China in recent years, selling 1.441 billion yuan at the box office and winning an award at the China New Era International Film Festival, while also gaining a lot of attention overseas. This study analyzes the accuracy of the English subtitles based on Newmark’s (1988) framework. In his model, Newmark (1988) assesses the accuracy by looking at the accurate reflection of the semantic, contextual, register and style of the ST in TT. Additionally, it adopts a questionnaire for non-Chinese speakers following Nababan, Nuraeni and Sumardiono’s (2012) approach to assess the acceptability and readability of the English subtitles. The significance of this study lies in its potential to enhance the quality of Chinese audiovisual products, reduce language barriers, foster effective cross-culture communication, and provide a valuable reference for the humor translation in Chinese comedy movies in the future.